2015
DOI: 10.1039/c5mb00018a
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis of two distinct stem-cell populations from human amniotic fluid

Abstract: Human amniotic fluid (AF) contains a variety of stem cells of embryonic and extra-embryonic origins.We characterized two distinct types of stem cells isolated from residual AF material derived from prenatal diagnostic amniocentesis. The two types of cells differed in their morphology and growth kinetics, showing fast (fast human amniotic stem cells; fHASCs) or slow (slow human amniotic stem cells; sHASCs) population-doubling times. Both fHASCs and sHASCs expressed pluripotent stem-cell markers, yet unlike sHAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The presented results confirmed that hAFSCs have potential to differentiate toward adipocyte, chondrocyte, and osteoblast cell line, which is consistent with the literature data [De Coppi et al, 2007;Saulnier et al, 2009;You et al, 2009;Phermthai et al, 2010;DeKoninck et al, 2014;Sousa et al, 2014;Romani et al, 2015].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The presented results confirmed that hAFSCs have potential to differentiate toward adipocyte, chondrocyte, and osteoblast cell line, which is consistent with the literature data [De Coppi et al, 2007;Saulnier et al, 2009;You et al, 2009;Phermthai et al, 2010;DeKoninck et al, 2014;Sousa et al, 2014;Romani et al, 2015].…”
Section: Discussionsupporting
confidence: 93%
“…Those cells secrete a wide variety of growth factors with complex feedback mechanisms among many types of immune cells [Murphy et al, ]. Recent discoveries of stem cells population in amniotic fluid have postulated that the well characterized amniotic fluid is a promising alternative source of fetal stem cells for therapy [Pappa and Anagnou, ; You et al, ; Da Sacco et al, ; Klemmt et al, ; Cananzi and De Coppi, ; Chun et al, ; Piskorska‐Jasiulewicz and Witkowska‐Zimny, ; Romani et al, ; Si et al, ]. It was observed during this study that within the primary culture, there are cells with different morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Written informed consent was obtained from each woman. HASCs were isolated and cultured as previously described [ 26 , 27 , 28 ]. Briefly, fresh amniotic fluid (3–5 mL) was centrifuged and the cell pellet cultured in 18% Chang B/2% Chang C media (Irvine Scientific, Ireland, UK) for 6–7 days to allow adherent cells to form colonies.…”
Section: Methodsmentioning
confidence: 99%
“…Cells with a predominantly fibroblast-like morphology and a colony shape similar to dermatoglyphics, appropriately characterized, represented HASCs and were cultured in MSCGM medium (Lonza, Gaithersburg, MD, USA). Since HASCs characterization in all the cases showed similarity in all the parameters considered for their characterization [ 26 , 27 , 28 ], only one HASC cell line was considered to recover EVs.…”
Section: Methodsmentioning
confidence: 99%
“…Even looking only at hAFSCs obtained during the second trimester (from amniocentesis), various classifications have been proposed for human amniotic subpopulations, including a morphological classification, since up to three cell types have been described, from epithelioid to spindle-shaped [6]. Therefore, amniocytes differ in many functional aspects, including survival rate, plastic adhesion, and growth characteristics.…”
Section: Introductionmentioning
confidence: 99%